2020
DOI: 10.1111/1756-185x.14022
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian antibodies among SLE women with premature menopause after cyclophosphamide

Abstract: Systemic lupus erythematosus (SLE) is a chronic inflammatory autoimmune disease with a relapsing-remitting course that affects multiple organs and tissues leading to a wide range of clinical manifestations. 1 SLE affects women more commonly than men with a ratio of 9:1, most commonly occurring in the child bearing age. 2,3 One of the most serious manifestations of SLE is renal disease (lupus nephritis), ranging from asymptomatic hematuria or proteinuria to serious nephritic and nephrotic syndrome, which can pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Indeed, cyclophosphamide, which is used as a first-line immunosuppressive medicine in the treatment of life-threatening organ involvement of SLE, SSc and vasculitides, is an alkylating agent that causes gonodotoxicity. Consistent with this general knowledge, recent studies showed an increased risk of ovarian failure in SLE patients treated with cyclophosphamide compared to SLE patients treated with mycophenolate, azathioprine, calcineurin inhibitors, and steroids [18][19][20]. For RA patients, there are inconsistent studies.…”
Section: Premature Ovarian Insufficiency In Autoimmune Diseasesmentioning
confidence: 78%
“…Indeed, cyclophosphamide, which is used as a first-line immunosuppressive medicine in the treatment of life-threatening organ involvement of SLE, SSc and vasculitides, is an alkylating agent that causes gonodotoxicity. Consistent with this general knowledge, recent studies showed an increased risk of ovarian failure in SLE patients treated with cyclophosphamide compared to SLE patients treated with mycophenolate, azathioprine, calcineurin inhibitors, and steroids [18][19][20]. For RA patients, there are inconsistent studies.…”
Section: Premature Ovarian Insufficiency In Autoimmune Diseasesmentioning
confidence: 78%
“…The choice of immunotherapy in infertile patients with autoimmune conditions is essential. The mainstay of treatment has included corticosteroids [ 18 ], whereas other immunosuppressive agents, such as cyclophosphamide, can cause premature ovarian failure, rendering IVF less effective [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the Tsaliki' group 33 undertook a study to determine whether the presence of ovarian autoimmunity also increased the risk of early ovarian failure among women receiving cyclophosphamide.…”
Section: Aoa Tests and Its Associated Challengesmentioning
confidence: 99%
“…However, no efforts were made by the group to check on the causative factors for these non‐specific false positives. On the other hand, the Tsaliki’ group 33 undertook a study to determine whether the presence of ovarian autoimmunity also increased the risk of early ovarian failure among women receiving cyclophosphamide. They demonstrated that AOA were present in a small percentage of patients, and that there was no suggestion of premature menopause to either level of these antibodies.…”
Section: Aoa Tests and Its Associated Challengesmentioning
confidence: 99%